Preparation method and application of hafnium dioxide film

By using oxide epitaxial growth technology to grow hafnium dioxide films on cubic oxide (111) substrates, the problem of uncontrollable preparation of hafnium dioxide films in the prior art is solved, and a high-performance ferroelectric film is realized, which is suitable for microelectronic devices.

CN119900083APending Publication Date: 2025-04-29UNIV OF SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510073151.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to controllably prepare hafnium dioxide thin films, resulting in their ferroelectric properties in microelectronic devices being affected.

Method used

The cubic oxide (111) crystal surface is used as the substrate to grow the hafnium dioxide thin film through oxide epitaxial growth technology to ensure that its crystal phase is a pure ferroelectric phase and its crystal direction is controllable and repeatable.

Benefits of technology

The grown hafnium dioxide film has obvious ferroelectricity, and its off-plane residual polarization intensity reaches 25μC/cm2 or higher, which significantly improves the performance in microelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900083A_ABST
    Figure CN119900083A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a hafnium oxide thin film, and the preparation method of the hafnium oxide thin film comprises the following steps: providing a substrate which is a crystal face (111) of a cubic oxide; and growing a hafnium oxide film on the surface of the substrate by adopting an oxide epitaxial growth technology. Growth of the hafnium oxide thin film is carried out from the two aspects of the substrate and the growth process, the crystalline phase of the grown hafnium oxide thin film is a pure ferroelectric phase, and the crystal orientation of the grown hafnium oxide thin film is controllable and repeatable. Tests show that the grown hafnium oxide film has obvious ferroelectricity, and the minimum out-of-plane remanent polarization of the hafnium oxide film can reach 25 mu C / cm < 2 >. The hafnium oxide thin film provided by the preparation method has important application prospects in the field of microelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of microelectronic devices, and specifically relates to a method for preparing a hafnium dioxide thin film and its application. Background Art

[0002] Hafnium dioxide (HfO2) is a ceramic material with a wide band gap and high dielectric constant. It has received extensive attention in the field of microelectronic devices in recent years. With the development of integrated circuits, the traditional silicon dioxide (SiO2) gate dielectric layer has reached its physical limit. Hafnium dioxide is considered to be an ideal material to replace traditional SiO2 due to its high dielectric constant, wide band gap, good thermal stability and compatibility with silicon substrate. In addition, hafnium dioxide also has ferroelectric properties, making it an excellent alternative to storage media in non-volatile memory.

[0003] Hafnium dioxide has many different crystal phases (including monoclinic phase, tetragonal phase, cubic phase and ferroelectric phase), among which the ferroelectric phase is a metastable phase, which usually appears under doping or specific conditions, and this phase does not appear naturally under normal pressure. In addition, hafnium dioxide can only be used in device applications if it is prepared into thin films. However, most of these thin films are polycrystalline films grown by atomic layer deposition (ALD). The crystal phase and crystal orientation of polycrystalline films are uncontrollable. The complex crystal structure formed in this way will greatly affect the ferroelectric properties of hafnium dioxide materials in electrode devices.

[0004] Therefore, it is urgent to study and develop a method for controllably preparing hafnium dioxide thin films. Summary of the invention

[0005] In view of this, the primary purpose of this application is to provide a method for preparing a hafnium dioxide thin film. The method uses the (111) crystal plane of cubic oxide as a substrate and uses oxide epitaxial growth technology to grow the hafnium dioxide thin film. The crystal phase of the grown hafnium dioxide thin film is a pure ferroelectric phase, and its crystal orientation is controllable and repeatable. According to tests, the grown hafnium dioxide thin film has obvious ferroelectricity, and its out-of-plane remanent polarization intensity can reach a minimum of 25μC / cm 2 .

[0006] In order to achieve the above objectives, this application adopts the following technical solutions:

[0007] One aspect of the present application provides a method for preparing a hafnium dioxide thin film, comprising the following steps:

[0008] Providing a substrate, wherein the substrate is a (111) crystal plane of a cubic oxide;

[0009] An oxide epitaxial growth technology is adopted to grow a hafnium dioxide film on the surface of the substrate.

[0010] Another aspect of the present application provides a hafnium dioxide film, wherein the crystal phase of the hafnium dioxide film is a pure ferroelectric phase, and the out-of-plane residual polarization intensity thereof is ≥25 μC / cm 2 .

[0011] Another aspect of the present application provides use of the hafnium dioxide thin film as described above in the preparation of a microelectronic device.

[0012] Another aspect of the present application provides a microelectronic device comprising the hafnium dioxide thin film described above.

[0013] Beneficial effects of this application:

[0014] The crystal phase of the hafnium dioxide film grown by the preparation method provided in this application is a pure ferroelectric phase, and the crystal orientation is controllable and repeatable. In addition, after testing, the out-of-plane remanent polarization intensity of the grown film is consistent with the theoretical prediction (the lowest can reach 25μC / cm 2 ), the hafnium dioxide film prepared in the present application can be applied to microelectronic devices such as non-volatile memory, thereby giving the microelectronic devices excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The figure is a process flow chart of preparing and characterizing hafnium dioxide thin films in a preferred embodiment of the present application.

[0016] Figure 2 This is a diagram showing the positional relationship between the target and the substrate in a preferred embodiment of the present application.

[0017] Figure 3 This is a diagram of the device structure prepared in Example 1.

[0018] Figure 4 This is a diagram of the structural characterization results in Example 1, wherein: Figure 4 a is the X-ray diffraction scanning result of hafnium dioxide film; Figure 4 b is the atomic force microscope test result of hafnium dioxide film; Figure 4 c is the reflection high energy electron diffraction pattern of the hafnium dioxide film; Figure 4 d is the pole figure scanning result of the hafnium dioxide film near 2θ≈29.88°.

[0019] Figure 5 This is the electrical performance test result diagram. DETAILED DESCRIPTION

[0020] The following will clearly and completely describe the implementation methods of the present application. The technical solutions in the implementation methods described below are exemplary and are only possible technical implementations of the present application, not all possible implementations. Those skilled in the art can fully combine the implementation methods of the present application to obtain other implementation methods without creative work, and these implementation methods are also within the scope of protection of the present application.

[0021] The first aspect of the present application discloses a method for preparing a hafnium dioxide film. The hafnium dioxide film preparation method of the present application combines substrate selection and growth process to prepare a hafnium dioxide film with a pure ferroelectric phase. The crystal orientation of the hafnium dioxide film is controllable, the process is repeatable, and the out-of-plane residual polarization strength of the grown hafnium dioxide film is high (the minimum can reach 25μC / cm 2 ), which has significant advantages.

[0022] In the present application, the method for preparing the hafnium dioxide thin film comprises the following steps:

[0023] S1. Provide a substrate, wherein the substrate is a (111) crystal plane of a cubic oxide

[0024] In the present application, the cubic oxide refers to a class of oxides with a cubic crystal structure, and its crystal structure presents cubic symmetry. Typical examples include, but are not limited to, perovskite oxides. Since the ferroelectric phase hafnium dioxide film belongs to the orthorhombic system, the cubic oxide has multiple crystal directions. In order to achieve better lattice matching, the substrate selects a cubic oxide, and the out-of-plane direction is the (111) crystal plane, which promotes the growth of orthorhombic phase hafnium dioxide along the (111) direction. In the present application, specific examples of the cubic oxide include strontium titanate (SrTiO3), lanthanum aluminate (LaAlO3), strontium tantalum aluminate ((La, Sr)(Al, Ta) O3), neodymium gallate (NdGaO3), dysprosium scandate (DyScO3), and gadolinium scandate (GdScO3), but are not limited thereto. Preferably, the cubic oxide is strontium titanate, and substrates of this material have a mature industrial chain, which facilitates the preparation method of the present application to achieve industrial-scale production.

[0025] It is understandable that there is no particular requirement for the thickness of the specific substrate, and those skilled in the art may make a specific selection based on actual needs, etc. In some specific embodiments of the present application, for ease of operation, preferably, the thickness h of the substrate satisfies 0<h≤1 mm.

[0026] In addition, the substrate is usually cleaned before use in the art, which is a common operation step in the art. It can be cleaned in a manner well known in the art, so no special instructions are given. In some specific embodiments of the present application, preferably, the substrate is wiped and cleaned with dust-free paper and alcohol until no obvious contaminants are visible on the surface of the substrate under a 5x microscope.

[0027] S2. Using oxide epitaxial growth technology, grow a hafnium dioxide thin film on the surface of the substrate.

[0028] In the present application, considering that the ferroelectric phase of the hafnium dioxide film needs to be realized under certain temperature and pressure, and the electrical properties of the hafnium dioxide film are greatly affected by internal oxygen vacancies, therefore, in order to avoid the degradation of film quality caused by oxygen vacancies, the present application preferably grows the film under a certain oxygen atmosphere. Therefore, after comprehensive consideration, the oxide epitaxial growth technology is selected.

[0029] In the present application, the oxide epitaxial growth technology is a method for depositing an oxide film on a substrate, which mainly includes pulsed laser deposition (PLD), oxide molecular beam epitaxy (OMBE), chemical vapor deposition (CVD) and chemical solution deposition (CSD). Among them, pulsed laser deposition (PLD) is to form an oxide film on a substrate by high-energy laser pulses; oxide molecular beam epitaxy (OMBE) is to form a neutral molecular beam in a vacuum environment by means of thermal evaporation and other means and deposit it on the substrate to form a film that continues the substrate lattice structure; while chemical vapor deposition (CVD) and chemical solution deposition (CSD) are to deposit an oxide film on a substrate by chemical reaction. These methods can all achieve the purpose of epitaxial growth of oxides on substrates. In some specific embodiments of the present application, the oxide epitaxial growth technology preferably used is pulsed laser deposition or oxide molecular beam epitaxy, and pulsed laser deposition is more preferably used.

[0030] It is understandable that those skilled in the art can select the above-mentioned oxide epitaxial growth technology based on needs without special requirements; in addition, there are no special limitations on growth parameters such as temperature, vacuum conditions, etc. Those skilled in the art can determine them through methods or experiments known in the art as needed. As long as the effects of the present application can be achieved, those skilled in the art have such ability.

[0031] In some specific embodiments of the present application, pulsed laser deposition is used as an example, and the target material used is preferably metal oxide-doped hafnium dioxide, wherein the metal oxide is one of yttrium oxide, zirconium oxide or cerium oxide.

[0032] For example, in some implementation cases, the target material is hafnium dioxide doped with yttrium oxide, and the doping amount W1 of the yttrium oxide satisfies 0%<W1≤10% according to the atomic ratio;

[0033] For example, in some other implementation cases, the target material is hafnium dioxide doped with zirconium oxide, and the doping amount W2 of the zirconium oxide is 0%<W2<100% according to the atomic ratio;

[0034] For example, in some other implementation cases, the target material is hafnium dioxide doped with cerium oxide, and measured in atomic proportion, the doping amount W3 of the cerium oxide satisfies 0%<W3≤12.5%.

[0035] In addition, there are no special requirements for the preparation of the target material in this application. Conventional processes in the art can be used, generally including the steps of grinding, tableting and sintering. No further details will be given here.

[0036] It is well known to those skilled in the art that the growth temperature, oxygen pressure and laser intensity etc. may affect the growth of thin films, and those skilled in the art may determine them by known methods or experiments as needed without any particular limitation. In some specific embodiments of the present application, in the pulsed laser deposition:

[0037] The growth temperature is preferably 700°C to 800°C, and may be, for example, any of 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C.

[0038] For oxygen pressure, 2×10 -2 Torr~6×10 -2 Torr, for example, can be 2×10 -2 Torr, 2.5×10 - 2 Torr, 3×10 -2 Torr, 3.5×10 -2 Torr, 4×10 -2 Torr, 4.5×10 -2 Torr, 5×10 -2 Torr, 5.5×10 - 2 Torr, 6×10 -2 Any value in Torr.

[0039] The laser intensity is preferably 2.0 J / cm 2 ~2.3J / cm 2 , for example, it can be 2.0 J / cm 2 , 2.1J / cm 2, 2.2J / cm 2 , 2.3J / cm 2 Any value in .

[0040] In addition, before the film growth begins, the reaction equipment is required to have a high vacuum degree to ensure that the target material inside the reaction equipment will not be contaminated by the external environment. Preferably, the vacuum degree of the reaction equipment is 10 -8 Torr or lower.

[0041] It is understandable that the thickness of the hafnium dioxide film grown in the present application has no special restrictions or requirements, and can be adjusted based on actual application requirements, etc. In some specific embodiments of the present application, preferably, the thickness of the hafnium dioxide film is 5nm to 100nm, for example, it can be any thickness of 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, but is not limited thereto.

[0042] It should be noted that when characterizing the electrical properties of the hafnium dioxide film, it is generally necessary to grow an additional bottom electrode. The material of the bottom electrode can be a relatively common type in the art, such as lanthanum strontium manganese oxide, or strontium ruthenate, but is not limited thereto. In some embodiments of the present application, its growth is also completed by a pulsed laser deposition device before the growth of the hafnium dioxide film. The specific growth conditions can be adjusted as needed, so there is no special limitation.

[0043] The second aspect of the present application discloses a hafnium dioxide film, which is prepared by the preparation method described above. By selecting a substrate and combining an oxide epitaxial growth process, the crystal phase of the prepared hafnium dioxide film is a pure ferroelectric phase. After testing, the out-of-plane residual polarization intensity is ≥25μC / cm 2 It is well known to those skilled in the art that the remanent polarization is an important property of ferroelectric materials, which can reflect the ability of ferroelectric materials to maintain polarization after the external electric field is lost. The magnitude of the remanent polarization can directly reflect the performance of the ferroelectric material in microelectronic devices.

[0044] The third aspect of the present application discloses the use of the hafnium dioxide thin film as described above in the preparation of microelectronic devices.

[0045] The fourth aspect of the present application discloses a microelectronic device, wherein the microelectronic device contains the hafnium dioxide thin film described above.

[0046] The hafnium dioxide film prepared by the preparation method of the present application has a pure ferroelectric phase and a high out-of-plane residual polarization intensity (the minimum can reach 25μC / cm 2), which is significantly better than the hafnium dioxide film produced by the existing process, and therefore has great application prospects.

[0047] In the present application, the microelectronic device includes but is not limited to any one of MOSFET, non-volatile memory, ferroelectric tunnel junction, logic element, and negative differential capacitor. For example, the hafnium dioxide film in the present application can be used as a high-k gate dielectric layer in MOSFET; it can also be used in non-volatile memory such as ferroelectric transistors; it can also be used as a ferroelectric storage layer in ferroelectric tunnel junctions; it can also be used as one of the gate components in logic elements; it can also be used as a dielectric in negative differential capacitors. But it is not limited to the above examples.

[0048] The following are specific embodiments of the present application. It should be noted that the following specific embodiments are only for illustrative purposes and do not limit the scope of the present application in any way.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0050] In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used are all commercially available.

[0051] Embodiment 1:

[0052] This embodiment provides a method for preparing a hafnium dioxide film, which can be found in Figure 1 , the specific steps are as follows:

[0053] (1) Equipment debugging: Turn on the mechanical pump of the pulsed laser deposition equipment to perform preliminary air extraction, then turn on the molecular pump. When the air pressure in the chamber reaches 10 -8 Torr or lower, it is sufficient for use.

[0054] (2) Substrate treatment: Take a strontium titanate (111) substrate (5 mm × 5 mm, thickness 0.5 mm), wipe and clean the substrate with dust-free paper and alcohol until no obvious contaminants are visible on the substrate surface under a 5x microscope.

[0055] (3) Prepare the target material: The target material in this embodiment is a cylinder with a bottom diameter of 25 mm and a height of 5 mm, which is made by mixing and pressing two powders of 93% hafnium dioxide and 7% yttrium oxide (atomic ratio, purity is 99.99%). Specifically, the mass of the required powder is calculated according to the expected target size, and then the corresponding mass of powder is weighed and poured into a mortar for uniform mixing; the uniformly mixed powder is poured into a tablet press and pressed, and the holding time and pressure are set to 15 minutes and 6 tons respectively; after the pressing is completed, the sample is taken out and placed in a tubular furnace for sintering, the sintering temperature is 1300°C, and the time is 7 hours; after the sintering is completed, the target material is obtained.

[0056] (4) Thin film growth: The growth temperature was set to 740°C and the oxygen pressure was set to 2×10 -2 Torr to 4×10 -2 Torr, laser intensity 2.1J / cm 2 , to grow the hafnium dioxide film, the specific steps are as follows:

[0057] First, the target and substrate are placed in the growth chamber through the sample transfer chamber twice (the sample transfer chamber and the growth chamber are two independent vacuum systems. The sample is first placed in the sample transfer chamber and then evacuated. Finally, the sample is placed in the growth chamber through the mechanical transfer rod. The vacuum degree in the growth chamber will not be destroyed during the whole process). The position relationship between the target and the substrate is as follows: Figure 2 As shown; then adjust the oxygen pressure, which can be determined by the oxygen input and the air pump exhaust volume; after setting, wait until the oxygen pressure reaches the target value to start heating, the equipment uses laser heating, and the heating rate is set to 50℃ / min; the laser intensity test should be completed before the temperature reaches the target temperature, the method is to control the laser generator to emit a laser with a frequency of 0.1Hz by outputting a pulse wave with a frequency of 0.1Hz through the function signal generator, and then use a laser energy meter to test at the laser output to obtain the laser energy intensity. Above, the required parameters are set, and the growth can be started. The growth stops after about 6000 pulses, and a hafnium dioxide film with a thickness of about 40nm is obtained after completion.

[0058] (5) In order to characterize the electrical properties of the ferroelectric hafnium dioxide film, an additional bottom electrode was grown in this embodiment. The lanthanum strontium manganese oxide material was used as the bottom electrode, and its growth was also completed by pulsed laser deposition equipment before the growth of the hafnium dioxide film. The temperature selected for the growth of the lanthanum strontium manganese oxide film (thickness of about 10nm) was 700℃, and the oxygen pressure was 3×10 -5 Torr, laser intensity 0.6 J / cm 2 What is grown at this time is a ferroelectric crystalline phase hafnium dioxide film / lanthanum strontium manganese oxide heterostructure, which can be used to characterize ferroelectric properties.

[0059] Figure 3The device structure is shown based on the ferroelectric crystalline phase hafnium dioxide film / lanthanum strontium manganese oxide heterostructure in Example 1. A gold electrode is plated on the surface of the sample by electron beam evaporation. The electrode size is 9500 μm. 2 Among them, STO is strontium titanate, and its chemical formula is SrTiO3; LSMO is lanthanum strontium manganese oxide, and its chemical formula is La 0.7 Sr 0.3 MnO3; Doped-HfO2 is doped hafnium dioxide.

[0060] Figure 4 Shown Figure 3 Test characterization results of the device shown in , where:

[0061] Figure 4 a is the X-ray diffraction scan result of the hafnium dioxide film. It can be seen that, except for the substrate peak, the X-ray diffraction peak has only one diffraction peak belonging to the polar orthorhombic phase of hafnium dioxide, which is consistent with the characteristics of a pure ferroelectric phase sample.

[0062] Figure 4 b is the atomic force microscopy test result of the hafnium dioxide film, which shows that the average roughness of the film surface is about 360 pm. The roughness of the picometer order is sufficient to explain the flatness of the film surface, which is consistent with the characteristics of a pure phase.

[0063] Figure 4 c is the reflection high-energy electron diffraction pattern of the hafnium dioxide film. It can be clearly seen that there are no polycrystalline "rings", but a series of "lattices", which is also consistent with the pure phase characteristics.

[0064] Figure 4 d is the pole figure scanning result of the hafnium dioxide film near 2θ≈29.88°, from which it can be concluded that the film is composed of eight polar orthorhombic phase domains with different out-of-plane directions, including two domains with out-of-plane crystal orientation (111) and two domains with out-of-plane orientation ( There are three crystal domains and the out-of-plane direction is There are three crystal domains, which conforms to the characteristics of a pure ferroelectric phase.

[0065] also, Figure 5 The PE curve test results of the grown film are shown. The test results of the electrical properties can prove that the hafnium dioxide film grown by the preparation method in this embodiment has obvious ferroelectricity, and its out-of-plane residual polarization intensity can reach 25μC / cm 2 Even higher, which is consistent with the theoretical results of pure ferroelectric phase.

[0066] Embodiment 2:

[0067] This embodiment provides another method for preparing a hafnium dioxide thin film. Compared with Embodiment 1, the growth conditions are different from those of Embodiment 1. The specific steps are as follows:

[0068] (1) Equipment debugging: same as in Example 1.

[0069] (2) Substrate treatment: same as in Example 1.

[0070] (3) Prepare target material: same as in Example 1.

[0071] (4) Thin film growth: The growth temperature was set to 780°C and the oxygen pressure was set to 5×10 -2 Torr to 6×10 -2 Torr, laser intensity 2.2J / cm 2 , grow the hafnium dioxide film, and the specific operating steps are the same as those in Example 1.

[0072] (5) In order to characterize the ferroelectric properties, a lanthanum strontium manganese oxide thin film was grown as the bottom electrode in the same manner and under the same conditions as in Example 1.

[0073] Embodiment 3:

[0074] This embodiment provides another method for preparing a hafnium dioxide film. Compared with Embodiment 1, the thickness of the grown hafnium dioxide film is different from that of Embodiment 1. The specific steps are as follows:

[0075] (1) Equipment debugging: same as in Example 1.

[0076] (2) Substrate treatment: same as in Example 1.

[0077] (3) Prepare target material: same as in Example 1.

[0078] (4) Thin film growth: set the temperature to 740°C and the oxygen pressure to 2×10 -2 Torr to 4×10 -2 Torr, laser intensity 2.1J / cm 2 , the hafnium dioxide film is grown, and the specific operation steps are the same as those in Example 1, except that the growth is stopped after about 4500 pulses, and a film with a thickness of about 30 nm is obtained after completion.

[0079] (5) In order to characterize the ferroelectric properties, a lanthanum strontium manganese oxide thin film was grown as the bottom electrode in the same manner and under the same conditions as in Example 1.

[0080] Table 1 shows the test characterization results of the hafnium dioxide thin films in Examples 1-3.

[0081] Table 1 Characterization results of hafnium dioxide films grown in Examples 1-3

[0082] Crystalline phase in the film <![CDATA[Remnant polarization intensity (μC / cm 2 )]]> Example 1 orthogonal phase 25 Example 2 orthogonal phase 25 Example 3 orthogonal phase 27

[0083] In addition, in order to further and more intuitively reflect the progress of the preparation method of the present application compared with the prior art, the present application conducted the following comparative test scheme.

[0084] Comparative Example 1:

[0085] This comparative example provides another method for preparing a hafnium dioxide thin film, which adopts the same implementation as Example 1, except that the substrate used is strontium titanate (001); the other process steps and parameter conditions are the same as Example 1. The growth process and the final film characterization results are shown in the following table:

[0086] Substrate selection Remanent polarization Crystalline phase in the film Comparative Example 1 Strontium titanate (001) <![CDATA[20μC / cm 2 ]]> Monoclinic phase, orthorhombic phase Example 1 Strontium titanate (111) <![CDATA[25μC / cm 2 ]]> orthogonal phase

[0087] It can be seen from the results in the above table that the residual polarization intensity of the hafnium dioxide film grown in the present application is relatively high, and the crystal phase is also single and controllable.

[0088] Comparative Example 2:

[0089] This comparative example provides another method for preparing a hafnium dioxide thin film, using the ALD method of growing a hafnium dioxide thin film in the prior art, which can be specifically referred to Müller J, U, TS, et al. Ferroelectricity in yttrium-doped hafnium oxide [J]. Journal of Applied Physics, 2011, 110 (11). The growth process and final film characterization results are shown in the following table:

[0090] Growth pattern Remanent polarization Crystalline phase in the film Comparative Example 2 ALD <![CDATA[24μC / cm 2 ]]> Monoclinic phase, orthorhombic phase Example 1 PLD <![CDATA[25μC / cm 2 ]]> orthogonal phase

[0091] It can be seen from the test results in the above table that the residual polarization intensity of the hafnium dioxide thin film grown in the present application is relatively high, and the crystal phase is also single and controllable.

[0092] Other parallel implementations

[0093] Embodiment 4:

[0094] This embodiment provides another method for preparing a hafnium dioxide thin film, which adopts the same implementation as that of embodiment 1, except that its growth conditions are different from those of embodiment 1. The specific steps are as follows:

[0095] (1) Equipment debugging: same as in Example 1.

[0096] (2) Substrate treatment: same as in Example 1.

[0097] (3) Prepare target material: same as in Example 1.

[0098] (4) Thin film growth: The growth temperature was set to 700°C and the oxygen pressure was set to 2×10 -2 Torr to 3×10 -2 Torr, laser intensity 2.3J / cm 2 , grow the hafnium dioxide film, and the specific operating steps are the same as those in Example 1.

[0099] (5) In order to characterize the ferroelectric properties, a lanthanum strontium manganese oxide thin film was grown as the bottom electrode in the same manner and under the same conditions as in Example 1.

[0100] Embodiment 5:

[0101] This embodiment provides another method for preparing a hafnium dioxide thin film, which adopts the same implementation as that of embodiment 1, except that its growth conditions are different from those of embodiment 1. The specific steps are as follows:

[0102] (1) Equipment debugging: same as in Example 1.

[0103] (2) Substrate treatment: same as in Example 1.

[0104] (3) Prepare target material: same as in Example 1.

[0105] (4) Thin film growth: The growth temperature was set to 800°C and the oxygen pressure was set to 4×10 -2 Torr to 6×10 -2 Torr, laser intensity 2.3J / cm 2 , grow the hafnium dioxide film, and the specific operating steps are the same as those in Example 1.

[0106] (5) In order to characterize the ferroelectric properties, a lanthanum strontium manganese oxide thin film was grown as the bottom electrode in the same manner and under the same conditions as in Example 1.

[0107] Embodiment 6-8:

[0108] This embodiment provides another method for preparing a hafnium dioxide thin film, which adopts the same implementation as that of embodiment 1, except that the substrate material is different from that of embodiment 1. Other process steps and growth conditions are the same as those of embodiment 1.

[0109] The substrates used in Examples 6-8 are lanthanum aluminate, strontium lanthanum tantalum aluminate, and dysprosium scandate, respectively.

[0110] Embodiment 9:

[0111] This embodiment provides another method for preparing a hafnium dioxide thin film, which adopts the same implementation as that of Embodiment 1, except that the growth process is oxide molecular beam epitaxy.

[0112] The hafnium dioxide films prepared in Examples 4-9 were tested and characterized in the same manner as in Example 1. The results showed that the crystal phases were all orthorhombic phases, and the out-of-plane remanent polarization intensity was ≥25 μC / cm 2 .

[0113] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a hafnium dioxide thin film, characterized in that: The following steps are involved: Providing a substrate, wherein the substrate is a (111) crystal plane of a cubic oxide; An oxide epitaxial growth technology is adopted to grow a hafnium dioxide film on the surface of the substrate.

2. The preparation method according to claim 1, characterized in that The cubic oxide is one of strontium titanate, lanthanum aluminate, strontium tantalum lanthanum aluminate, neodymium gallate, dysprosium scandate, and gadolinium scandate; Preferably, the cubic oxide is strontium titanate.

3. The preparation method according to claim 1, characterized in that: The thickness h of the substrate satisfies 0<h≤1mm.

4. The preparation method according to claim 1, characterized in that: The oxide epitaxial growth technology is one of pulsed laser deposition, oxide molecular beam epitaxy, chemical vapor deposition, and chemical solution deposition; Preferably, the oxide epitaxial growth technique is pulsed laser deposition or oxide molecular beam epitaxy; Preferably, the oxide epitaxial growth technique is pulsed laser deposition.

5. The preparation method according to claim 4, characterized in that: In the oxide epitaxial growth technology, the target material used is hafnium dioxide doped with metal oxide, wherein the metal oxide is one of yttrium oxide, zirconium oxide or cerium oxide; Preferably, the target material is hafnium dioxide doped with yttrium oxide, and the doping amount W1 of yttrium oxide satisfies 0%<W1≤10% according to the atomic ratio; Preferably, the target material is hafnium dioxide doped with zirconium oxide, and the doping amount W2 of the zirconium oxide is 0%<W2<100% according to the atomic ratio; Preferably, the target material is hafnium dioxide doped with cerium oxide, and measured in atomic ratio, the doping amount W3 of the cerium oxide satisfies 0%<W3≤12.5%.

6. The preparation method according to claim 4, characterized in that: In the pulse laser deposition, the growth temperature is 700°C to 800°C, and the oxygen pressure is 2×10 -2 Torr~6×10 -2 Torr, laser intensity 2.0 J / cm 2 ~2.3J / cm 2 .

7. The preparation method according to claim 1, characterized in that: The thickness of the grown hafnium dioxide film is 5nm-100nm.

8. A hafnium dioxide thin film, characterized in that: The hafnium dioxide film is prepared by the preparation method according to any one of claims 1 to 7, wherein the crystal phase of the hafnium dioxide film is a pure ferroelectric phase, and its out-of-plane residual polarization intensity is ≥25μC / cm 2 .

9. Use of the hafnium dioxide film according to claim 8 in the preparation of microelectronic devices; Preferably, the microelectronic device is any one of MOSFET, non-volatile memory, ferroelectric tunnel junction, logic element, and negative differential capacitor.

10. A microelectronic device, characterized in that: A hafnium dioxide thin film comprising the hafnium dioxide thin film according to claim 8; Preferably, the microelectronic device is any one of MOSFET, non-volatile memory, ferroelectric tunnel junction, logic element, and negative differential capacitor.

Citation Information

Patent Citations

  • Preparation method of silicon-doped HfO2-based ferroelectric film

    CN110218979A

  • Method for preparing HfO2 film by adopting pulse laser molecular beam epitaxy

    CN110295348A

  • Method for producing ferroelectric film, ferroelectric film, and usage thereof

    US20220178012A1

  • Ferroelectric thin film, electronic device, and production method

    WO2016031986A1